Elevated Infant Mortality Rate among Dutch Oral Cleft Cases: A Retrospective Analysis from 1997 to 2011 - van Nunen, Daan P. F.; van den Boogaard, Marie-José H.; Don Griot, J. Peter W.; Rüttermann, Mike; van der Veken, Lars T.; Breugem, Corstiaan C. (Frontiers in Surgery, 2014)
Objectives: First, to determine the infant mortality rate for Dutch patients with isolated oral clefts as well as for patients with clefts seen in association with other malformations. Second, to conduct a similar analysis per cleft type: cleft lip with or without cleft palate, cleft palate (including Robin sequence). Third, to examine the underlying causes of death. Material and methods: A retrospective review of the charts of patients with oral clefts born in the period 1997-2011 and treated in three regional cleft centers in the Netherlands. Results: 1530 patients with oral clefts were born during the study period and treated in the cleft centers. The overall infant mortality rate for all clefts was 2.09%, significantly higher than the general Dutch infant mortality rate of 0.45%. In a subanalysis per cleft type the infant mortality rates were 1.22%, 1.38%, 2.45% and 3.62% for cleft lip, cleft lip with cleft palate, cleft palate and Robin sequence. The mortality rates for isolated oral clefts did not differ significantly from the general Dutch rate. Causes of death were congenital malformations of the heart in 40.6%, airway / lungs in 15.6%, nervous system in 15.6%, infectious disease in 12.5% and other or unknown in 15.6%. Conclusion: The elevated infant mortality rate observed in Dutch patients with oral clefts is almost exclusively caused by associated congenital malformations. After diagnosis of an oral cleft an in-depth medical examination and a consult by the pediatrician and clinical geneticist is imperative to instigate the appropriate medical management.